Mucuna laticifera, a new species from north-eastern India - Ingalhalikar, Shrikant; Page, Navendu; Gaikwad, Swaroopsingh; Gurav, Rajaram V (Phytotaxa, 2017)
Mucuna laticifera, a new species of Fabaceae from Sikkim state of India is described and illustrated here. It can be distinguished from its closely related species by the presence of a watery latex, uniformly green to pale yellow corolla, glabrous standard and wings and parallel pod margins.